Clinical and psychological status analysis of children and parents infected with familial aggregation omicron variant in Shanghai in parent-child ward. Issue 12 (December 2022) - Li, Miaochen; Wu, Zhimin; Bian, Xiangli; Jiang, Qin; Fan, Sainan; Zhang, Kun; Guo, Zhi; Hui, Lei; Guo, Miaomiao; Zhen, Fang; Zhang, Jinping
Abstract: Aims: To analyze the clinical characteristics, treatment outcomes and sleep psychological problems of children and parents infected with familial aggregation Omicron variants under a parent-child ward treatment mode to provide a theoretical reference for the diagnosis and comprehensive treatment of Omicron variant strains. Methods: The clinical data of 225 children and 230 adult family members admitted were retrospectively collected and analyzed to investigate their clinical characteristics and response to treatments. Results: The proportion of infected adults and children was the same, and the proportion of children with mild disease was higher than that of adults, but the clinical symptoms were milder. The clinical symptoms of fever, nausea, vomiting and wheezing in children were significantly higher than in adults (P < 0.05). In addition, dry pharynx, pharynx itching and pharyngeal pain were lower than in adults (P < 0.05). The time of turning negative in the moderate group was longer than in the mild group, and the time of turning negative in the unvaccinated group was higher than in the vaccinated group (P < 0.05). The Cycle Threshold Value (Ct value) of Open Reading Frame 1ab (ORF1ab) and Nucleocapsid protein (N) gene of children were higher adults. The increase in the rate of Ct value of ORF1ab and N gene in adults treated with Traditional Chinese Medicine (TCM) was significantly higher than in those who underwent symptomatic treatment (P < 0.01). Based on the Children's Sleep Habits Questionnaire (CSHQ)score, we found varying levels of sleep problems in sleeping habits, latency and anxiety, night awakenings and abnormal sleep at all ages (P < 0.05). In the adult group, those with Self-Rating Scale of Sleep (SRSS) scores ≥3 accounted for more than 50% of adults with insomnia, sleep deprivation, sleep instability and early awakening. The proportion of adults with anxiety and depression was 21.3% and 16.4%. Conclusion: Infections in children and adults during this pandemic were mainly associated with familial aggregation infections, and their clinical symptoms were mainly located in the upper respiratory tract. With comprehensive treatment, children became negative faster, vaccination led to faster recovery, and although some patients experienced sleeping and psychological issues, all patients had good prognoses following comprehensive diagnosis under a parent-child ward treatment mode. Abstract : Omicron; Variants; COVID-19; Family cluster infection; Clinical features; Treatment outcome; Psychological sleep; Family ward.